ACE2 in the Gut: The Center of the 2019-nCoV Infected Pathology - Guo, Yuexin; Wang, Boya; Gao, Han; Gao, Lei; Hua, Rongxuan; Xu, Jing-Dong (Frontiers in Molecular Biosciences, 2021)
The 2019-nCoV is a rapidly contagious pneumonia caused by the recently discovered coronavirus. Although generally the most noticeable symptoms concentrated in the lung, the disorders in the gastrointestinal tract are of great importance in the diagnosis of 2019-nCoV. The angiotensin converting enzyme 2 (ACE2), an important regulator of many physiological functions including blood pressure and nutrients absorption, is recently identified as a vital entry for 2019-nCoV to enter host cells. In this review, we summarize its functions both physiologically and pathologically. We also elaborate its conflicting roles from the clews of contemporary researches which may provide significant indications for pharmacological investigations and clinical uses.